The sedimentology of the Zerrissene turbidite system, Damara Orogen, Namibia - Swart, Roger (Rhodes University, Faculty of Science, Department of Geology, 1991)
The Zerrissene turbidite system of central-western Namibia is a late Proterozoic sequence which consists of dominantly siliciclastic turbidites interbedded with minor turbiditic and hemipelagic marbles. The basin in which these sediments were deposited is located at the junction of the coastal and intra-cratonic arms of the Pan-African Damara Orogen, and an understanding of the sedimentary evolution of this basin is therefore important to the understanding of the development of the orogen as a whole. One major and two minor phases of folding have deformed the sediments, but the grade of metamorphism is low and sedimentary structures are often well preserved. Further, the area lies entirely within the Namib Desert and the lack of vegetation cover results in good outcrops providing an unusual opportunity for examining a large Precambrian turbidite system. The system consists of five formations: three siliciclastic and two mixed carbonatesiliciclastic units. The floor of the system is not exposed, and the oldest sedimentary rocks which outcrop are siliciclastics of the Zebrapiits Formation. This is overlain successively by the Brandberg West Formation (dominantly calcareous), the Brak River Formation (siliciclastic), the Gemsbok River Formation (calcareous) and the Amis River Formation (siliciclastic). Nine silicilastic turbidite facies have been recognised in the basin. These are facies Aâ‚‚ (disorganised onglomerates), Bâ‚ (horizontally laminated to massive greyackes), Câ‚‚ ("classical" turbidites), Dl (sandstone-shale couplets with base cut-out Bouma sequences), Dâ‚‚ (sandstone-shale couplets with less sand than shale and base cut-out Bouma sequences), E (coarse, discontinuous sandstone-shale couplets), F (slumped units), G (shale) and H (glacial dropstones). Four facies are associated with the carbonate horizons, and these carbonate facies are given the suffix c to distinguish them from similar siliciclastic facies. These are facies Ac (disorganised and graded marble breccias), facies Cc (graded carbonates), facies Gc (hemi-pelagic marbles) and facies G (pelagic shales). The basal Zebrapiits Formation is made up of relatively thin packages of thin- to thickbedded, laterally continuous facies Dâ‚ , Dâ‚‚ and Bâ‚ beds encased in thick envelopes of shale. This type of sequence is typical of a distal lobe-fringe, and requires an unconfined basin-floor on which it can develop. The overlying Brandberg West Formation consists of a basal portion of interbedded facies Cc and G, followed by a sequence dominanted by facies Gc. This sequence is interpreted as representing outer-apron carbonate turbidites, derived from multiple point sources (facies Cc), with background pelagic settling (facies G) overlain by hemi-pelagic deposits (facies Gc). A reversal back to siliciclastic turbidites followed with deposition of the Brak River Formation. This sequence comprises relatively thick packages of laterally continuous facies Bâ‚ , Dâ‚ , and Dâ‚‚ beds sandwiched between facies G shales, a succession characteristic of a lobe to lobe-fringe environment with intermittent abandonment of lobes. An unconfined basin floor adjacent to a passive margin is required for the development of this type of sequence. Glacial dropstones (facies H) are found in the upper portions of this formation, and slumped beds are also present (facies F), but are uncommon. The facies F beds are only found in association with facies H and are therefore considered to be genetically related. Slumping of beds was possibly caused by an oversupply of sediment from ice-rafting which caused instability. The overlying Gemsbok River Formation has a sequence similar to the Brandberg West Formation in that the basal portion consists of interbedded facies Cc and G, which is overlain by a thick sequence of largely facies Gc beds. Minor facies Ac beds occur near the top of the overall sequence. This formation is interpreted as an outer-apron succession with the facies Ac beds representing distal inner-apron deposits, indicating progradation of the system. The youngest unit in the basin, the Amis River Formation, shows strong lateral variation from west to east. In the west the sequence comprises laterally continuous facies Bâ‚ , Câ‚‚, Dâ‚ and Dâ‚‚ with rare, discontinuous facies E beds. Facies G is relatively minor in the sequence. In the east the succession is dominated by facies Dâ‚ , Dâ‚‚ and G, and this succession is interpreted as a sequence of distal turbidites which were deposited on a basin-plain. The system developed by aggradation rather than progradation as only minor cycles are developed. Geochemical and petrological features indicate that the entire siliciclastic system was derived from a granite-recycled orogen terrane. Palaeocurrent data are unreliable because of the deformation, but transport was initially from the south-west, moving later to the west and north-west. The provenance of the carbonates is uncertain as reliable palaeocurrent indicators are rare, but they could have been derived either from South America or from the extensive carbonate deposits developed on the north-western margins of the basin. The Zenissene siliciclastic turbidite system represents the distal portion of a major submarine turbidite system, the more proximal parts of which now lie west of the exposed basin, either under the Atlantic Ocean or in eastern South America. The calcareous deposits developed as an apron adjacent to a multiple point source, the position of which is at present unknown.
Keywords: Sedimentology; Sediments (Geology) -- Namibia; Sedimentation and deposition; Turbidites